2014
DOI: 10.1371/journal.pone.0099859
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Interleukin-7 mRNA Transcripts in Chinese Tree Shrew (Tupaia belangeri chinensis)

Abstract: Interleukin-7 (IL7) is a pleiotropic cytokine that is actively involved in the immune system. The Chinese tree shrew (Tupaia belangeri chinensis) has been proposed as an alternative experimental animal to primates in biomedical research. However, there is a lack of biological knowledge about the immune system of the tree shrew. In this study, we cloned the IL7 gene (tIL7) in the Chinese tree shrew and quantified the expression of mRNA transcripts in eight tissues (heart, liver, spleen, lung, kidney, intestine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
(52 reference statements)
0
11
0
1
Order By: Relevance
“…The primary hepatocytes were prepared by two-step collagenase perfusion [44] to get the primary hepatocytes cells (TSHC). The different tissues including kidney, lung, skin and the thoracic aorta, were collected to isolate the primary cells as described previously [45–47]. Primary rat skin and aorta cells were isolated and cultured in similar protocol to the Tree Shrews.…”
Section: Methodsmentioning
confidence: 99%
“…The primary hepatocytes were prepared by two-step collagenase perfusion [44] to get the primary hepatocytes cells (TSHC). The different tissues including kidney, lung, skin and the thoracic aorta, were collected to isolate the primary cells as described previously [45–47]. Primary rat skin and aorta cells were isolated and cultured in similar protocol to the Tree Shrews.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous report, Yu et al . also determined the tree shrew IL7 mRNA sequences 23 , and the CDS predicted by our method matched the canonical form of tree shrew IL7 mRNA transcript (accession number: JQ182399). These results showed that gene sequence predictions based on the combination of genome and RNA sequencing were more accurate than those based on genome sequencing alone.
Figure 2Analysis of the accuracy of the gene sequences predicted on the basis of the combined genome and RNA sequencing.
…”
Section: Resultsmentioning
confidence: 99%
“…Then, 500 ng of RNA was reverse transcribed to cDNA using the EasyScript One-Step gDNA Removal and cDNA Synthesis SuperMix (TransGen Biotech, Beijing, China).RT-PCR was performed with a PCR Mix(Invitrogen, USA) according to the manufacturer’s protocol. The expression of BZLF1,LMP1,EBNA1,EBNA2 and EA was determined by RT-PCR using the primers,including 4 primers we designed for RT-PCR, as follows:BZLF1: 5′-GCG GAC AAA AAT CAG GCG TT-3′ and 5′-GAA AAT GCC GGG CCA AGT TT-3′; LMP1:5′-AAT TTG CAC GGA CAG GCA TT-3′ and 5′-AAG GCC AAA AGC TGC CAG AT-3′; EBNA2: 5′-AAC TCC TGG CCC ATC CAA TG-3′ and 5′-GGA GGG GCG AGG TCT TTT AC-3′; EA: 5′-AAC GAG CAG ATG ATT GGG CA-3′ and 5′-CGT GGT GAC GTA GAG ATC CG-3′ and 1 primers previously reported [ 60 ]: EBNA1: 5′-GTC ATC ATC ATC CGG GTC TC-3′ and 5′-TTC GGG TTG GAA CCT CCT TG-3′.The “housekeeping gene” β-actin was amplified as an internal control using the primers previously described [ 61 ], and cDNA from B95–8 cells was used as a positive control.…”
Section: Methodsmentioning
confidence: 99%